Biocontrol and growth promotion potential of Bacillus velezensis NT35 on Panax ginseng based on the multifunctional effect - Li, Xueqing; Wang, Jiarui; Shen, Hang; Xing, Chenxi; Kong, Lingxin; Song, Yu; Hou, Wanpeng; Gao, Jie; Jiang, Yun; Chen, Changqing (Frontiers in Microbiology, 2024)
Abstract: The Bacillus velezensis strain NT35, which has strong biocontrol ability, was isolated from the rhizosphere soil of Panax ginseng. The antifungal effects of the NT35 strain against the mycelium and spore growth of Ilyonectria robusta, which causes ginseng rusty root rot, were determined. The inhibitory rate of I. robusta mycelial growth was 94.12% when the concentration of the NT35 strain was 107 CFU·mL-1, and the inhibitory rates of I. robusta sporulation and spore germination reached 100% and 90.31%, respectively, when the concentration of the NT35 strain was 104 CFU·mL-1 and 108 CFU·mL-1, respectively. Strain NT35 had good prevention effects against ginseng rust rot indoors and in the field with the control effect 51.99%, which was similar to that of commercial chemical and biocontrol agents. The labelled strain NT35-Rif160-Stre400 was obtained and colonized ginseng roots, leaves, stems and rhizosphere soil after 90 days. B. velezensis NT35 can induce a significant increase in the expression of five defensive enzyme-encoding genes and ginsenoside biosynthesis-related genes in ginseng. In the rhizosphere soil, the four soil enzymes and the microbial community improved during different periods of ginseng growth in response to the biocontrol strain NT35. The NT35 strain can recruit several beneficial bacteria, such as Luteimonas, Nocardioides, Sphingomonas, and Gemmatimonas, from the rhizosphere soil and reduce the relative abundance of Ilyonectria, Fusarium, Neonectria and Dactylonectria, which cause root rot and rusty root rot in ginseng plants. The disease indices were significantly negatively correlated with the abundances of Sphingomonas and Trichoderma. Additionally, Sphingomonadales, Sphingomonadaceae and actinomycetes were significantly enriched under the NT35 treatment according to LEfSe analysis. These results lay the foundation for the development of a biological agent based on strain NT35.